Cerchysiella mesosae Yang sp. nov. (Hymenoptera: Encyrtidae), a parasitoid of Mesosa myops (Dalman) (Coleoptera: Cerambycidae) larvae in China - Yang, Zhong-Qi; Wang, Xiao-Yi; Cao, Liang-Ming; Tang, Yan-Long; Tang, Hua (Zootaxa, 2013)
Cerchysiella mesosae Yang sp. nov. (Hymenoptera: Chalcidoidea: Encyrtidae), is described from China. It is a gregarious koinobiont endoparasitoid in mature larvae of Mesosa myops (Dalman) (Coleoptera: Cerambycidae), a wood boring pest of many broad-leaved tree species in China, particularly Quercus mongolica and Q. liaotungensis (Fagaceae) in forest areas of northeasternChina. The new species is one of the principal natural enemies of the wood borer and it may have potential as a biological control agent for suppression of the pest.